Therapeutic Effects of Amnion-Conjugated Chitosan-Alginate Membranes on Diabetic Wounds in an Induced Diabetic Swine Model: An In Vitro and In Vivo Study - Jeong, Woonhyeok; Hong, Jamin; Jung, Minho; Jang, Mijin; An, Sanghyun; Jo, Taehee; Kwon, Sunyoung; Son, Daegu (Archives of Plastic Surgery, 2022)
Background Chitosan (CS) is a well-known antimicrobial dressing material. Moreover, widely used amniotic membranes contain growth factors beneficial for wound healing. Herein, we created a novel amnion-conjugated CS-alginate membrane dressing and tested its wound healing potency in a diabetic swine model.Methods The bovine amniotic powder growth factor contents were evaluated by protein assay, and the powder's wound healing effects were assessed in vitro by HaCaT cell scratch closure. In vivo, two minipigs developed streptozotocin-induced diabetes. Serial serum glucose measurements and intravenous glucose tolerance tests were performed to confirm their diabetic status. Twelve square-shaped wounds created on each pig's back were randomly divided into control (n = 4), CS (n = 4), and amnion-CS (AC; n = 4) groups and treated accordingly with different dressings. Wound healing in each group was assessed by measuring wound contraction over time, capturing wound perfusion with indocyanine green (ICG) angiography, and histologically analyzing inflammatory markers.Results Amniotic powder elution promoted HaCaT cell migration in the scratch wound model, suggesting its beneficial in vitro wound healing effects. In vivo, the CS and AC groups showed earlier wound contraction initiation and reepithelialization and earlier wound perfusion improvement by ICG angiography than the control group. Additionally, the wound size of the AC group at week 3 was significantly smaller than those in the control group. There was no significant difference in the numbers of acute and chronic inflammatory cells between the groups.Conclusion The amnion-conjugated CS-alginate membrane, as well as CS dressing alone, could be a favorable dressing option for diabetic wounds.
Keywords: amnion; chitosan; wound healing; diabetes; swine